2018
DOI: 10.1016/j.bjm.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of GeneXpert MTB/RIF assay and LED-FM microscopy for the diagnosis of extra pulmonary tuberculosis in Khyber Pakhtunkhwa, Pakistan

Abstract: GeneXpert is one of the recent technological instruments used to diagnose tuberculosis in a short span of time. In this study, the performance of GeneXpert MTB/RIF assay for the diagnosis of extrapulmonary tuberculosis (EPTB) was compared with light-emitting diode Fluorescent Microscopy (LED-FM) in Khyber Pakhtunkhwa, Pakistan. A total of 737 EPTB samples were collected from tuberculosis (TB) suspected patients. Out of these samples, male to female ratio was 53% (n = 390) to 47% (n = 347) respectively. The sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
3
13
1
2
Order By: Relevance
“…The school children showed a high percentage of meningitis and lymphadenitis. However, the study showed a close relationship with the study in Beijing children hospital (Wu et al, 2012) The present study showed close relation with the results of Khan et al (Khan et al, 2018), who reported a 40-50% sensitivity of Gne Xpert more than LED-FM microscopy (Abdelwahab et al, 2020). Furthermore, the present study showed agreement with the results where Gene Xpert was a more effective technique in comparison to the ZN technique as detection rate was 62.1% and 41.6% for Gene Xpert and ZN respectively (Chinedum et al, 2017…”
Section: Discussionsupporting
confidence: 88%
“…The school children showed a high percentage of meningitis and lymphadenitis. However, the study showed a close relationship with the study in Beijing children hospital (Wu et al, 2012) The present study showed close relation with the results of Khan et al (Khan et al, 2018), who reported a 40-50% sensitivity of Gne Xpert more than LED-FM microscopy (Abdelwahab et al, 2020). Furthermore, the present study showed agreement with the results where Gene Xpert was a more effective technique in comparison to the ZN technique as detection rate was 62.1% and 41.6% for Gene Xpert and ZN respectively (Chinedum et al, 2017…”
Section: Discussionsupporting
confidence: 88%
“…Figure 1 showed the flowchart of the research collection, while Table 1 provided a summary of the included studies. Of the nine studies included, three were carried out in Pakistan 10 , 13 , 15 , two were conducted in South Africa 12 , 14 , and the rest were carried out in Turkey 17 , Iran 9 , China 16 , and Spain 11 . All studies used a prospective observational design.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the risk of bias in the subject preference area, six studies 9 , 10 , 12 , 14 , 16 , 17 were labeled as low risk, two studies 13 , 15 were labeled as high risk, and one study 11 was labeled as an unclear risk because it did not explain the exclusion criteria clearly. The reason for the high risk of bias in this domain was due to inappropriate exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of samples evaluated in each study ranged from 21 to 302, with a median value of 96. Overall, eight (67%) studies were carried out in high-burden TB countries, where the TB prevalence was 63-267 per 100 000 population (Chen et al, 2019;Jing et al, 2017;Khan et al, 2018;Kim et al, 2015;Li et al, 2017;Pang et al, 2017;Samuel et al, 2018;Sharma et al, 2014). Four (33%) studies were conducted in low-burden TB countries, where the TB incidence was 0.81-7.5 per 100 000 population (Habous et al, 2019;Hillemann et al, 2011;Mazzola et al, 2016;Tortoli et al, 2012).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%